Riociguat for treatment of pulmonary hypertension in COPD: a translational study. Issue 6 (27th June 2019) - Pichl, Alexandra; Sommer, Natascha; Bednorz, Mariola; Seimetz, Michael; Hadzic, Stefan; Kuhnert, Stefan; Kraut, Simone; Roxlau, Elsa T.; Kojonazarov, Baktybek; Wilhelm, Jochen; Gredic, Marija; Gall, Henning; et al.
Chronic obstructive pulmonary disease (COPD), which comprises the phenotypes of chronic bronchitis and emphysema, is often associated with pulmonary hypertension (PH). However, currently, no approved therapy exists for PH-COPD. Signalling of the nitric oxide (NO)–cyclic guanosine monophosphate (cGMP) axis plays an important role in PH and COPD. We investigated the treatment effect of riociguat, which promotes the NO–cGMP pathway, in the mouse model of smoke-induced PH and emphysema in a curative approach, and retrospectively analysed the effect of riociguat treatment on PH in single patients with PH-COPD. In mice with established PH and emphysema (after 8 months of cigarette smoke exposure), riociguat treatment for another 3 months fully reversed PH. Moreover, histological hallmarks of emphysema were decreased. Microarray analysis revealed involvement of different signalling pathways, e.g. related to matrix metalloproteinases (MMPs). MMP activity was decreased in vivo by riociguat. In PH-COPD patients treated with riociguat (n=7), the pulmonary vascular resistance, airway resistance and circulating MMP levels decreased, while oxygenation at rest was not significantly changed. Riociguat may be beneficial for treatment of PH-COPD. Further long-term prospective studies are necessary to investigate the tolerability, efficacy on functional parameters and effect specifically on pulmonary emphysema in COPD patients. The soluble guanylate cyclase stimulator riociguat reverses fully established cigarette smoke-induced pulmonary emphysema and hypertension in mice, and may have beneficial effects on PH in patients presenting with both PH and moderate COPD http://ow.ly/dGgL30oj7LC